Practical microkinetic modeling approach for methanol synthesis from syngas over a Cu-based catalyst - Park, Jongmin; Cho, Jiyeong; Lee, Yongkyu; Park, Myung June; Lee, Won Bo (Industrial and Engineering Chemistry Research, 2019)
In this study, a practical strategy to develop a microkinetic model for methanol synthesis from syngas over a Cu-based catalyst is described. The comprehensive model consists of forward and backward reactions of 28 possible elementary-step reactions for CO and CO2 hydrogenation and the water−gas shift reaction. A combination of ab initio density functional theory (DFT) and semiempirical unity bond index−quadratic exponential (UBI-QEP) methods was used to determine the heat of adsorption and activation energies. DFT calculations confirmed that formate (HCOO**) adsorbs in a bidentate fashion and provided the enthalpies and adsorption energies of gas and surface intermediates for subsequent UBI-QEP calculations. The pre-exponential factors were estimated from the order of magnitude of the transition state theory as the initial values and by fitting the experimental data, thus reducing the computational load by not calculating the vibrational frequencies and partition functions for translational, rotational, and vibrational motions. For the reactor model, partial equilibrium ratios were used to reduce the stiffness of the microkinetic model. The most plausible reaction pathways were suggested by considering relatively fast step reactions, while the surface reaction of H3CO* and H* was found to be the rate-determining step by the degree of rate control. The developed model was also used to evaluate the effects of the temperature, pressure, and H2 fraction in the feed on the methanol synthesis rate to elucidate the suitable operating conditions. The model effectiveness was validated by comparison with other reported works. The proposed approach can be further exploited for the efficient development of other microkinetic models.
Keywords: Ab initio density functional theories (DFT); Adsorption energies; Forward-and-backward; Microkinetic modeling; Preexponential factor; Rate determining step; Surface intermediates; Transition state theories